Abnormal psychology - Comer, Ronald J.; Comer, Jonathan S. (2021)
"Psychology textbook, focusing on the study of Abnormal Psychology, with integrated coverage of theory, diagnosis, and treatment, and from an inclusive, cross-cultural perspective"--